Penerapan Aplikasi Investasi Online untuk Masyarakat Indonesia (Studi Kasus di Jawa) - Masno Marjohan; Jeni Andriani; Annisa Nurlita Putri (ITB AAS INDONESIA, 2023)
This study aims to analyze and determine the effect of performance goals, intention to use, business expectations, social conditions, trust and perceptions of risk affecting intentions to use online investment applications among Indonesian people, especially the people of Banten, West Java and Special Region of Jakarta. This research is an explanatory research where quantitative data for hypothesis testing is obtained through a cross-sectional survey using an online questionnaire. This study uses a questionnaire, quantitative research centers on statistical analysis of numerical data collected using large-scale survey research, from the results of 511 users of online investment applications analyzed using PLS-SEM. The results revealed that performance expectations, effort expectations, facilitation conditions, trust, and perceived risk had a significant positive effect on intentions to use online investment applications in Indonesia. Meanwhile, social influence has no significant effect on the intention to use online investment in Indonesia. The findings of this study may be useful for the private sector, which can learn more about their customers' preferences in choosing online investment applications to invest their money in Indonesia. In addition, research findings can be used to identify opportunities, mitigate risks, assess reputation, and uncover barriers such as lack of awareness, deception, and skepticism.